2015
DOI: 10.1002/bmc.3547
|View full text |Cite
|
Sign up to set email alerts
|

An LC‐MS/MS method for simultaneous determination of cefprozil diastereomers in human plasma and its application for the bioequivalence study of two cefprozil tablets in healthy Chinese volunteers

Abstract: A rapid and sensitive liquid chromatography-tandem mass spectrometric method was developed for the first time and validated for the determination of cefprozil diastereomers in human plasma. The plasma samples were prepared by protein precipitation using acetonitrile. Detection was performed using an electronic spray ion source in the negative ion mode, operating in the multiple reaction monitoring of the transitions m/z 388.0 to m/z 205.0 for cefprozil diastereomers and m/z 346.1 to m/z 268.1 for cephalexin (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Both diastereomers had similar t 1/2 values of 1.87 and 1.66 h, respectively. The T max and t 1/2 values for cefprozil were similar to those previously reported in healthy Chinese volunteers [ 22 ], while the C max values were a little higher than, but still similar to, those seen in Korean volunteers [ 12 ]. The AUC 0-t values were 42.4 ± 10.4 μ g·h/mL for cis -cefprozil and 3.85 ± 1.4 μ g·h/mL for trans -cefprozil in the current study, which were approximately 40% higher than those in a previous Chinese study, but similar to those in the Korean study [ 12 ].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Both diastereomers had similar t 1/2 values of 1.87 and 1.66 h, respectively. The T max and t 1/2 values for cefprozil were similar to those previously reported in healthy Chinese volunteers [ 22 ], while the C max values were a little higher than, but still similar to, those seen in Korean volunteers [ 12 ]. The AUC 0-t values were 42.4 ± 10.4 μ g·h/mL for cis -cefprozil and 3.85 ± 1.4 μ g·h/mL for trans -cefprozil in the current study, which were approximately 40% higher than those in a previous Chinese study, but similar to those in the Korean study [ 12 ].…”
Section: Resultssupporting
confidence: 86%
“…Because cefprozil is composed of cis and trans isomers in an approximately 9:1 ratio, it is necessary to use a more sensitive method to detect the trans isomer. So far, the reported methods for detecting cefprozil isomers have used an electrospray ion source in negative ion mode [ 17 , 22 ]. In the current study, we not only improved the HPLC method using an acetonitrile/water LC gradient, achieving baseline chromatographic separation of the isomers within 4 minutes, but also found greater sensitivity for determination of cefprozil in positive rather than negative ion mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper estimation ofCEF bioavailability should be conducted to avoid prospective side effects such as the generation of microbial resistance [3]_ENREF_5. Liu et al (2016) suggested that the bioequivalence conductance based on CFZ only can be enough [4]. However, the FDA draft guidance for CEF determination is still regulating total CEF determination for bioequivalence conductance.…”
Section: Introductionmentioning
confidence: 99%
“…Method development for CEF diastereoisomers determination in the biological sample is a critical process due to the stereo-isomeric structure [5]. Several methodshave been reported for CEF determination in plasma samples [4,[6][7][8][9][10][11][12]_ ENREF_2_ENREF_2. The recent published paper by He et al (2018) show proper sensitivity and simplicity [12], however,itsuffer reliability which will be illustrated later.In this vein, a primary objective for this work was to introduce a simple, valid and reliablemethods for CEF diastereoisomers determination in human plasma.…”
Section: Introductionmentioning
confidence: 99%